The hideout - Bunting, Eve, 1928- (San Diego : Harcourt Brace Jovanovich, 1991)
Feeling unloved by his mother and new stepfather, Andy hides out in a luxurious San Francisco hotel and stages his own kidnapping in order to obtain ransom money to pay for a trip to England to see his father.
Booklist.
School Library Journal.
Wilson's Junior High School.
6.3
4-6
5-8
Keywords: Kidnapping -- Fiction; Parent and child -- Fiction; Runaways -- Fiction; Kidnapping -- Fiction; Parent-child relationship -- Fiction; Runaway children -- Fiction